Trends in Interactive Visualization - Zudilova-Seinstra, Elena (Springer, 2017)
This unique, multi-disciplinary volume provides an insight into an active and vital area of research – Interactive Visualization. Interactive Visualization enables the development of new scientific techniques to view data, and to use interaction capabilities to interrogate and navigate through datasets and better communicate the results.